Contribution to the study of the narrative code of calendar verbal rituals, on the basis of verbal code of ritual and customary complex "vodici" in Macedonia - Rękas, Joanna (Anafora, 2022)
The primary objective of the study is to find and describe the narrative code of calendar verbal rituals, defined as an unalienable word of the living present. The term narrative code determines a system of rules that has a crucial impact on defining the principles of selecting and combining the elements of the story, i.e. heroes, space, time and plot. The sources for the analysis are verbal rituals excerpted from the ritual and customary practice Vodice (epiphany) in Macedonia. The analysis demonstrated a strong dependence of intratextual narration (i.e. the story creating a work of verbal folklore) on extratextual narration (social and religious). Using the following theories: 1. the memory of religious groups (Maurice Halbawchs), 2. collective and cultural memory (Assmann Jan, Astrid Erll) and 3. commemorative ceremonies (Paul Connerton), has shown how the foundational scenes of extratextual social (change in status) and religious (defined role in the festivities) narration are present in the ritual and customary practice of the Feast of Epiphany.